The Potential Effect Of Ethanolic Extract Rambusa Leaf (Passiflora foetida L.) As Anti-inflamation To Male Mice (Mus musculus) - Wijaya, Duma Aji; Ovikariani; Saptawati, Tunik (STIKES Telogorejo Semarang, 2022)
One of the plants known as herbal medicine in Central Java is Brambutan or Rambusa. This research conducted on experimental animal using ethanol extract of rambusa leaf (Passiflora foetida L.) which has an anti-inflammation effect on reducing edema. The carrageenan used-induced feet edema was 1 % and animal subjects were grouped into 5 categories for different treatments, namely the administration of 1 % colloidal Na-CMC solution, diclofenac sodium solution, ethanol extract with various doses of 250 mg/kg body weight, 500 mg/kg body weight, and 750 mg/kg body weight given orally. By the time after 1 hour, the edema volume on mice feet measured until 6 hours. The data showed that the 1 % Na-CMC colloidal solution given did not affect the percentage of edema reduction (0 %), the subject group was given 250 mg/kg body weight and 500 mg/kg body weight showed a decrease level of edema (0.01 %), the group was given 750 mg/kg body weight decreased edema (0.02 %), and diclofenac sodium solution group showed decrease level of edema (0.04 %). In this study, it can be concluded that the ethanol extract of rambusa leaf (Passiflora foetida L.) has the highest anti-inflammation and anti-inflammation effect at a dose variation of 750 mg/kg body weight with a 0.02 % reduction in edema